Sensory marketing and the cross modal correspondences : The effect of product colour on the perception of product odour - Starostová, Adriana (2019)
The purpose of this dissertation is to investigate the role of colour on the perception of odour by measuring the a) preference and b) intensity of 16 possible combinations of 4 coloured bottles and 4 odours as rated by 297 participants (130 males and 167 females). The two way ANOVA for preference revealed that the role of both – colour and odour is significant for Czech participants, but the significance increases with the cultural homogeneity as for Slavic nationals, the colour and odour did not play a significant role in their preference ratings. In contrary to previous research, the effect of colour and odour on intensity ratings was not significant. Linear regression analysis then showed that gender is also a significant factor and males are generally more prone to give higher preference scores by 5.58 % than females to colour and odour interactions. On the other hand, a choice of preferred colour did not affect the preference scores. In addition, several types of congruencies between colour and odour were proposed. It is argued that one of these types (perceptual, semantic, mixed) reflect the decision making about preference levels more precisely. As a result, it has been demonstrated that intuitive congruent pairings of colours and odours (such as lemon and yellow) do not increase the preference ratings among consumers. Instead, the mixed semantical perceptual congruency corresponds significantly to the collected data. This approach could simplify product testing methods where the colour and odour are deemed to be selected variables.